Accurate modelling and synthesis of the Lead 11 ECG signal - Shorten, Gavin P. (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2012)
This thesis is a study of Lead II ECG signal synthesis. The principal problem of EGG signal synthesis is two fold, the first concerns the accuracy of the instrument used to deliver the synthesised signal and the second concerns the correlation between the synthesised signal and the characteristics of in vivo EGG. This research addresses both problems with the design of an accurate EGG signal generator and the characterisation of the timing of the EGG Lead II signal.
Keywords: Electronic & Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin.